TCreERT2, a Transgenic Mouse Line for Temporal Control of Cre-Mediated Recombination in Lineages Emerging from the Primitive Streak or Tail Bud - Anderson, Matthew J.; Naiche, L. A.; Wilson, Catherine P.; Elder, Cindy; Swing, Deborah A.; Lewandoski, Mark (PloS one, 2013)
The study of axis extension and somitogenesis has been greatly advanced through the use of genetic tools such as the TCre mouse line. In this line, Cre is controlled by a fragment of the T (Brachyury) promoter that is active in progenitor cells that reside within the primitive streak and tail bud and which give rise to lineages emerging from these tissues as the embryonic axis extends. However, because TCre-mediated recombination occurs early in development, gene inactivation can result in an axis truncation that precludes the study of gene function in later or more posterior tissues. To address this limitation, we have generated an inducible TCre transgenic mouse line, called TCreERT2, that provides temporal control, through tamoxifen administration, in all cells emerging from the primitive streak or tail bud throughout development. TCreERT2 activity is mostly silent in the absence of tamoxifen and, in its presence, results in near complete recombination of emerging mesoderm from E7.5 through E13.5. We demonstrate the utility of the TCreERT2 line for determining rate of posterior axis extension and somite formation, thus providing the first in vivo tool for such measurements. To test the usefulness of TCreERT2 for genetic manipulation, we demonstrate that an early deletion of ß-Catenin via TCreERT2 induction phenocopies the TCre-mediated deletion of ß-Catenin defect, whereas a later induction bypasses this early phenotype and produces a similar defect in more caudal tissues. TCreERT2 provides a useful and novel tool for the control of gene expression of emerging embryonic lineages throughout development.